DYNAMICS OF THE PSYCHOPHYSICAL STATE OF FUTURE LAW ENFORCEMENT OFFICERS IN THE COURSE OF THEIR PROFESSIONAL TRAINING - Holovanova, I.A.; Gorbenko, D.A.; Ostapovich, V.P.; Okhrimenko I.М.; Kryvolapchuk, V.O.; Lyakhova, N.A.; Okhrimenko, S.S. (World of Medicine and Biology, 2023)
The research aimed to investigate the dynamics of indicators of physical and mental states of cadets, i.e. future lawenforcement officers in the course of their training at a higher educational institution with specific learning environment. The research involved 96 male cadets aged 17–20 who entered the National Academy of Internal Affairs in 2018. The research lasted 4 years. Cadets’ physical state was assessed by the indicators of their body weight, body length, age, heart rate, and blood pressure and was determined by the formula of the physical state index proposed by Ye. A. Pirohova. Cadets’ mental state was assessed by the indicators of situational anxiety (methodology of Ch. D. Spielberger, Yu. L. Khanin) and well-being, activity, and mood (“WAM”). A significant improvement in cadets’ physical state index during the first and second years of their training (p < 0.05–0.001) and an insignificant deterioration in the third training year (p ˃ 0.05) was revealed. At the same time, the level of cadets’ anxiety significantly (p < 0.001) decreases during their training, and their emotional state improves. This indicates the effectiveness of professional training of future law enforcement officers in general and physical training in particular. However, the deterioration of the physical state index in cadets during the third year of their training proves the need to improve the educational process in the academic subject area referred to as “Special Physical Training” by increasing the share of general physical training.